2015
DOI: 10.15348/1980-6906/psicologia.v17n2p185-198
|View full text |Cite
|
Sign up to set email alerts
|

Perfil Cognitivo dos Alunos com Dificuldades de Aprendizagem na Leitura e Matemática

Abstract: Resumo: A coocorrência entre as dificuldades na leitura e na matemática é frequente, indicando que as habilidades cognitivas comuns subjacentes a tais dificuldades possam estar deficitárias. A pesquisa aqui descrita analisa as habilidades cognitivas que estão na base das aprendizagens da leitura e da matemática, contribuindo para a prática pedagó-gica nessas áreas. Trata-se de um estudo transversal de caráter quantitativo em que foram identificadas funções cognitivas de 79 alunos do 3º ao 6º ano do ensino fund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 11 publications
0
11
0
10
Order By: Relevance
“…Analysis has been conducted on cognitive differences between children with alterations only in reading/writing, those with alterations only in arithmetic and those with alterations in both skills. 18 It was observed that children with more complex cognitive alterations (as in working memory, phonological awareness, numerical sense and others) are the ones that have difficulties in both domains (language and arithmetic). However, children with difficulties only in arithmetic also presented some alterations in linguistic skills, such as narrative memory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis has been conducted on cognitive differences between children with alterations only in reading/writing, those with alterations only in arithmetic and those with alterations in both skills. 18 It was observed that children with more complex cognitive alterations (as in working memory, phonological awareness, numerical sense and others) are the ones that have difficulties in both domains (language and arithmetic). However, children with difficulties only in arithmetic also presented some alterations in linguistic skills, such as narrative memory.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis has been conducted on cognitive differences between children with alterations only in reading/writing, those with alterations only in arithmetic and those with alterations in both skills. 18 It was observed that children with more complex cognitive alterations (as in working memory, phonological awareness, numerical sense and others)…”
Section: Statistical Analysis Of the Datamentioning
confidence: 99%
See 1 more Smart Citation
“…En la UFRGS (Universidade Federal do Río Grande do Sul) otro grupo investigación describió las habilidades implicadas en la coocurrencia de dificultades con la lectura y las matemáticas (Corso & Dorneles, 2015). Recientemente aplicaron intervenciones (ver la sección Dificultades en el aprendizaje de las matemáticas, más arriba) en un esfuerzo por mejorar el rendimiento de los niños con ADHD (Sperafico et al, 2019).…”
Section: Preguntas Específicas Sobre La Cognición Numérica En Brasilunclassified
“…Esses resultados evidenciam a necessidade de uma discussão mais profunda sobre os elementos envolvidos no ensino e na aprendizagem de tais áreas. Um relevante passo nesse sentido é compreender que, embora as aprendizagens da leitura e da matemática possam caracterizar processos específicos, existem relações entre elas, e as especificidades de uma área acabam influenciando a outra DORNELES, 2015). Também há o importante papel das competências de base, especificamente as funções executivas (FE).…”
Section: Introductionunclassified